Irradiation by a low-energy pulsed electron beam of zirconia-based composite; Gas Discharge Plasmas and Their Applications (GDP 2019) - Leonov A. A. Andrey Andreevich; Ivanov Yu. F. Yuriy Fedorovich; Kalashnikov M. P. Mark Petrovich; Paygin V. D. Vladimir Denisovich; Teresov A. D. (2019, 2019)
Заглавие с титульного экрана